HUBUNGAN TINGKAT KECEMASAN PADA PRE ANESTESI DENGAN KEJADIAN PONV PADA PASIEN GENERAL ANESTESI DI RSUD SEJIRAN SETASON BANGKA BARAT - Zilvia Harlina ,; Septian Mixrova Sebayang ,; Eza Kemal Firdaus , (Jurnal Cakrawala Ilmiah, 2024)
This study aims to determine the relationship between general anesthesia patient anxiety and the incidence of PONV at the RSUD Sejiran Setason West Bangka. This type of research is quantitative research with Spearman Rank correlation data analysis. In this case, the research variables are the anxiety level of general anesthesia patients and the incidence of PONV. Measuring the level of patient anxiety using the Hamilton Rating Scale for Anxiety (HRS-A) instrument and measuring the incidence of PONV using an observation sheet. The sample for this study was 30 patients with general anesthesia at Sejiran Setason Hospital, West Bangka in August 2023. The sample selection for this study used consecutive sampling technique. The results of the research showed that the level of general anesthesia patients anxiety at Sejiran Setason Hospital, West Bangka Regency was mild anxiety as much as 67%, moderate anxiety as much as 30%, and severe anxiety as much as 3%. Meanwhile for no anxiety and very severe anxiety it is 0%. In the case of PONV incident in a sample of general anesthesia patients in the category of nausea only was 40%, nausea and vomiting was 13%, and 47% did not experience PONV. The results of the Spearman rank analysis showed that the relationship between anxiety and the incidence of PONV in general anesthesia patients at Sejiran Setason Regional Hospital, West Bangka Regency had a low correlation, in the same direction, and the relationship between the two variables was not significant.